A study of dense-medium cyclone inner-wall abrasion based on ultrasonic phased array technology. (October 2018) - Gangfeng, Zheng; Wandong, Xia; Xiaoming, Wu; Yingchun, Yan
Abstract: Directing at the problem that dense-medium cyclone is abraded by materials while conventional detection method can't make real-time and highly efficient detection of defects, this paper introduced working process and imaging principle of ultrasonic phased array technology in details. And then through experimental research of dense-medium cyclone model, it drew the conclusion that ultrasonic phased array technology could conduct real-time imaging display of dense-medium cyclone inner-wall abrasion defects and the error was within 8%.